Entre fenómeno y proceso: sobre la "História Global da Literatura Portuguesa" - Gonçalves Neto, Nefatalin (Madrygal. Revista de Estudios Gallegos, 2024)
Review of the book Global History of Portuguese Literature, edited by Annabela Rita, Isabel Ponce de Leão, José Eduardo Franco, and Miguel Real, with coordination by Carlos F. Clamote Carreto, Isabel Morujão, Micaela Ramon, Maria Luísa Malato, Luísa Paolinelli, Dionísio Vila Maior, and Maria do Carmo Cardoso Mendes (Lisbon: Temas e Debates, 2024), by Nefatalin Gonçalves Neto.